2001
DOI: 10.1104/pp.125.4.2007
|View full text |Cite
|
Sign up to set email alerts
|

Active Oxygen Produced during Selective Excitation of Photosystem I Is Damaging Not Only to Photosystem I, But Also to Photosystem II

Abstract: With the aim to specifically study the molecular mechanisms behind photoinhibition of photosystem I, stacked spinach (Spinacia oleracea) thylakoids were irradiated at 4°C with far-red light (Ͼ715 nm) exciting photosystem I, but not photosystem II. Selective excitation of photosystem I by far-red light for 130 min resulted in a 40% inactivation of photosystem I. It is surprising that this treatment also caused up to 90% damage to photosystem II. This suggests that active oxygen produced at the reducing side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 37 publications
6
55
1
Order By: Relevance
“…Plants with decreased content of PsaF or PsaD had a low PSI activity and hence a strong tendency to overreduction of the intersystem chain, which made PSII highly susceptible to photodamage (Haldrup et al, 2000(Haldrup et al, , 2003Ihnatowicz et al, 2004). PSI with impaired function can also generate reactive oxygen, which may directly damage PSII (Tjus et al, 2001). In either case, the compromised photosynthesis will make it difficult for the plant to generate the energy required for PSII repair, thereby further exacerbating PSII photodamage.…”
Section: Discussionmentioning
confidence: 99%
“…Plants with decreased content of PsaF or PsaD had a low PSI activity and hence a strong tendency to overreduction of the intersystem chain, which made PSII highly susceptible to photodamage (Haldrup et al, 2000(Haldrup et al, , 2003Ihnatowicz et al, 2004). PSI with impaired function can also generate reactive oxygen, which may directly damage PSII (Tjus et al, 2001). In either case, the compromised photosynthesis will make it difficult for the plant to generate the energy required for PSII repair, thereby further exacerbating PSII photodamage.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive irradiance causes the overproduction of harmful ROS that in turn damage the photosynthetic apparatus (Asada 1999, Downs et al 2002. Lightdependent ROS production occurs in chloroplasts, involving several possible pathways in both PS I and PS II (Badger 1985, Richter et al 1990, Tjus et al 2001, where the Mehler reaction (Mehler 1951) generates hydrogen peroxide (H 2 O 2 ) from superoxides (Downs et al 2002). Consequently, highly permeable H 2 O 2 would be removed efficiently by increasing mass transfer rates, from zooxanthellae to the surrounding water mass via the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it may also indicate the presence of O 2 -• besides 1 O 2 . In isolated membrane preparations, superoxide radicals have been implied to participate in photoinhibition as products of electron transport to oxygen both in functioning (Miyao 1994) and in donor-side impaired PSII (Chen et al 1995), and recently in PSI (Tjus et al 2001), although their production was not confirmed with spin trapping EPR spectroscopy (Hideg et al 1995). In our experiments, HO-1889NH was less sensitive to 1 O 2 than DanePy (Table 1), and its fluorescence was quenched to a smaller extent than in that of DanePy in spinach leaves exposed to excess PAR (Fig.…”
Section: Infiltration Methods Of Ros Sensors and Their Effect On Photmentioning
confidence: 99%